IMPLEMENTATION OF INTERNATIONAL PUBLIC SECTOR ACCOUNTING STANDARDS BY DEVELOPING COUNTRIES - Bohdan Zasadnyi; Natalia Konovalenko (Економіка та суспільство)
The purpose of the article is to provide a comprehensive understanding of the implementation of International Public Sector Accounting Standards (IPSAS), drawing on case studies and empirical evidence. Harmonization of financial reporting in the public sector has been a significant accounting reform initiative in recent years. IPSAS have emerged as an international benchmark for evaluating these changes. This article reviews scientific literature on the transition to IPSAS in developing countries, analyzing how transition to IPSAS helps building accountability in public sector. The methods used include a systematic review of scientific articles, case studies, and reports from international organizations. The article aims to offer insights into the practical aspects of IPSAS adoption and to identify key factors that contribute to successful implementation.